Design Process Reuse Based on Genetic Engineering - Shurong Tong; Bo Li; Keqin Wang (2007 IEEE International Conference on Industrial Engineering and Engineering Management, 2007)
Product design process has essential traits and behavior bearing an analogy with the genetic traits of organisms. Based on this point of view, this paper introduces an idea that genetic engineering into design process reuse. Firstly, types of process knowledge required in process reuse are studied. The extraction and representation of process bases are also discussed. Secondly, the design process gene model supporting process reuse are constructed according the relationship between process bases and the ordered sequence of process base pairs and the relationship between process genome and design objectives. Thirdly, the design process reuse model is presented based on the mechanism of heredity and mutation of organism, which includes inheriting original process and adding new process gene. By using process gene model into design process reuse, the efficiency and quality of product design will be improved.